Gobierno Corporativo y Corrupción Empresarial en las Empresas Estatales - Vega Carrasco, Gian Carlo (2022)
Currently, according to the latest survey of perception on corruption in Perú corruption is the second biggest problem for the country, the first being citizen insecurity. In recent years, Peru has experienced many corruption scandals closely related to private sector companies, such as the Lava Jato, Club de la Construcción cases, among others; where the participation of public companies under private law such as Petro Perú stands out. For this reason, it is proposed to promote tools such as the governance of the principles of good corporate governance as a mechanism for the prevention of corporate corruption.